Effect of the modified Atkins diet on NLRP3, caspase-1, IL-1β, and IL-10 in patients with tetralogy of Fallot undergoing open-heart surgery: A randomized controlled trial - Yanuarso, Piprim B.; Djer, Mulyadi M.; Hendarto, Aryono; Pudjiadi, Antonius H.; Rachmadi, Lisnawati; Wibowo, Heri; Advani, Najib; Murni, Indah K.; Kekalih, Aria; Sukardi, Rubiana; Dilawar, Ismail; Susanti, Dhama S.; Supriatna, Novianti (Narra Sains Indonesia, 2025)
Cardiopulmonary bypass in tetralogy of Fallot (TOF) corrective surgery induces hyperinflammation by activating NLRP3, caspase-1, and interleukin-1β (IL-1β), subsequently triggering an interleukin-10 (IL-10) response. Despite its known metabolic and anti-inflammatory effects, the impact of the modified Atkins diet (MAD) in pediatric cardiac surgery remains unexplored, with no studies on its use in TOF patients undergoing open-heart surgery. The aim of this study was to assess the effect of MAD on the expression of NLRP3, caspase-1, IL-1β, and IL-10, in TOF patients undergoing open-heart surgery. A double-arm, randomized-controlled trial was conducted with 44 TOF patients. The treatment group (n=22) received the MAD, a low-carbohydrate, high-fat regimen with unrestricted fat and protein intake for at least 14 days preoperatively, while the control group (n=22) followed a standard diet without carbohydrate restriction. Blood plasma and infundibulum heart tissues were collected for analysis. Whole blood samples were collected using a winged infusion needle before the intervention, an Abbocath infusion needle after 14 days of intervention, and a syringe without a needle connected to an arterial line in patients undergoing open-heart surgery at 6, 24, and 48 hours post-surgical correction. Infundibulum heart tissues were collected during the open-heart surgery. This study demonstrated significant differences in NLRP3 protein expression (p=0.015), caspase-1 protein expression (p=0.001), and IL-10 levels between before intervention and 6-, 24-, and 48-hours post-surgery in the MAD group compared to the control group. In contrast, no significant differences in IL-10 levels were observed in the control group between before intervention and 48 hours post-surgery (p=0.654). In conclusion, MAD may modulate perioperative inflammation in TOF patients undergoing open-heart surgery by downregulating NLRP3 and caspase-1 expression while sustaining IL-10 levels. Despite reduced NLRP3 and caspase-1 expression, unchanged IL-1β levels indicate alternative regulatory mechanisms.